Adolescent Beliefs about Antisocial Behavior: Mediators and Moderators of Links with Parental Monitoring and Attachment - Andrew Dane; Richard Kennedy; Mary Spring; Anthony Volk; Zopito Marini (International Journal of Emotional Education, 2012)
The current study examined whether parental monitoring and attachment were related to adolescent beliefs about antisocial acts, with temperament, gender, and age considered as potential moderators. A total of 7135 adolescents, ages 14-18 years, completed self-report measures of antisocial beliefs, parental monitoring, attachment security, and temperament. Results indicate that both attachment security and parental monitoring are associated with adolescent beliefs about antisocial behaviour. It also appears that the two aspects of parenting are complementary, in that a secure attachment relationship is associated with greater parental monitoring knowledge, which in turn is linked with a lower tolerance for antisocial behaviour. However, the relations between these aspects of parenting and beliefs about antisocial acts depended on the young people's characteristics, with some results varying by age, gender and temperament. Implications for future research and parent-focused interventions to prevent antisocial beliefs and behaviour are discussed.